The Effect Of Profitability, Company Size, Socail Responsibility, And Capital Structure On Firm Value In Companies In The Consumer Goods Industry Sector Indonesia - Muhid, Abdul; Mujiyati; Putriani, Santi (Jurnal Economic Resource, 2024)
The consumer goods industry in Indonesia constitutes a significant component of the national economy. The sector is confronted with significant challenges posed by the forces of globalization and digital disruption, which necessitate a continuous process of adaptation and innovation on the part of companies. The objective of this study is to examine the impact of profitability, company size, social responsibility (CSR), and capital structure on firm value. This study employs descriptive statistical analysis and multiple regression analysis to assess the interrelationships between the independent and dependent variables. The results demonstrate that profitability exerts a positive influence on firm value, while company size and social responsibility exert negative influences on firm value. Capital structure, on the other hand, exerts a positive influence on firm value. Collectively, these variables account for 93.8% of the variation in firm value, indicating a significant interdependence among them. The study concludes with practical implications for stakeholders in the consumer goods sector, suggesting that increasing profitability and reviewing capital structure can improve firm valuation